ANALYSIS OF DROPSHIPPING AND RESELLER BUSINESS MODELS AS A LOW-RISK E-COMMERCE STRATEGY - Auwalu Shuaibu Muhammad; Umu Farikhatus Sa’bandiyah; Ary Dean Amri; Wilda Anjelisvintya Munawaroh; Syindi Putriana Dwi Febri Rohma; Yulia Juwita (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
This article discusses the analysis of dropshipping and reseller business models as a low-risk e-commerce strategy. Dropshipping and reseller are two popular methods used by business actors to run a business online without the need to manage the stock of goods directly. This research aims to explore the advantages and disadvantages of both business models, as well as how they can be attractive alternatives for beginner entrepreneurs or those who want to reduce financial risks in running an e-commerce business. The results of the analysis show that while both models offer significant profit potential, the risks associated with product quality, delivery, and price competition remain major challenges. However, with the right strategy, both dropshipping and reseller can be an effective option to start a business with limited capital and more controlled risks. This analysis discusses the benefits, risks, and long-term implications of each model on customer satisfaction and business sustainability. The results are expected to provide strategic guidance for e-commerce business players in choosing the right model according to their risk profile and business goals in designing and developing efficient and sustainable business strategies.